A Multimodal Analysis of the Construction of Material and Spatial Meaning in the Interior of Saminah Sihyadi Mosque - Primastiti Wening Mumpuni; Diana Safinda Asran; Anisah Rahmawati; Asaya Zila Putri Tori (Institut Seni Indonesia Surakarta, 2026)
Mosques are not merely places of worship; they also serve as complex cultural texts where spatial design and material elements express layered social and symbolic meanings. This study investigates how the interior of Masjid Saminah Sihyadi, an urban mosque in Surakarta, Indonesia, constructs meaning through its material configuration, spatial zoning, and symbolic elements. Using a Multimodal Discourse Analysis (MDA) approach, the research focuses on materials such as rattan and open-cell metal ceilings, pivoted krepyak windows, and copper calligraphy panels. Data were collected through visual documentation, on-site observation, and informal interviews with mosque users. The findings reveal a nuanced narrative embedded in material choices: rattan signifies warmth and intimacy, typically associated with female prayer zones, while exposed metal reinforces spatial dominance and masculine order. The pivot windows mediate openness and social fluidity, and the copper calligraphy marks spiritual authority and sacred presence. These material-spatial arrangements actively participate in shaping religious experience, gendered spatial perception, and socio-cultural narratives. This research contributes to a deeper understanding of interior architecture in religious spaces, highlighting how design operates as an agent of cultural meaning-making.